Renungan Warisan Sumpah Pemuda Terhadap Lunturnya Rasa Nasionalisme Akibat Penggunaan Bahasa Gaul dalam Media Sosial pada Generasi Z - Jehan, Siti Aqila Noor; Firmansyah, Kiki Dwi; Arriani, Alya; Pratama, Haikal Azka (Suara Bahasa, 2025)
The use of slang by generation Z which is increasingly widespread due to the influence of social media can affect the use of good and correct Indonesian. This research aims to analyze the phenomenon of the use of slang in generation Z in social media which is feared to undermine the sense of nationalism because it contradicts the legacy of the youth pledge, namely Indonesian. The method used in this research is a descriptive method with a qualitative approach. The data collection used was by conducting interviews with five respondents while listening and recording the data obtained. After that, the researcher identified two main aspects, namely the impact of slang on social media among generation Z and generation Z's attitude towards the frequent use of slang rather than good and correct Indonesian. The results of this study show that Generation Z tends to use more slang in their daily lives, both in real life and on social media. The use of Indonesian language in accordance with the rules is only used in certain formal situations such as academic environments by most of generation Z. The conclusion of this study is that generation Z realizes that slang can make nationalism fade because they almost always use slang and forget the use of Indonesian language according to the rules